The Body as Gendered Discourse in British and French Costume and Heritage Fictions - Pidduck, Julianne (Cinémas)

(untitled) (Cinémas, 2012)
This article explores several articulations between gender and genre in contemporary British and French costume and heritage fiction. Genre is defined here both as a (gendered) discourse of cultural value that shapes the cultural meaning of costume and heritage fiction, and as a symbolic negotiation of shared cultural concerns. Through case studies of Elizabeth (Shekhar Kapur, 1998) and Lady Chatterley et l’homme des bois (Pascale Ferran, 2006), the author examines changing generic accounts of female desire and sexuality, analyzing both textual and discursive framings of gender and other differences. These films exemplify an emergent attention to the body in intensive states of pleasure and suffering as a form of generic renewal in some recent British and French films. The broader theoretical ambition of the article is to explore how the body operates as a highly coded gendered and generic discourse in costume and heritage fiction.